ความสัมพันธ์ระหว่างความรู้เท่าทันสื่อ กับการได้รับอิทธิพลด้านการกำหนดความสำคัญแก่วาระข่าวสาร และการเลือกกรอบในการตีความข่าวสาร - ฟารีดา เตชะวรินทร์เลิศ (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
The objective of this research is to study the relationship between media literacy and agenda Setting and framing effect. Researcher wonders whether newspapers have the same effects of agenda Setting and framing on perception to students who differ in levels of media literacy. The methodologies of this study are survey research by using questionnaires to collect data from 375 students and content analysis of 4 daily Thai popular newspapers: ThaiRath, DailyNews, Kom-Chad-Leuk and KhaoSod. This findings indicate that media literacy has no significant relationship with agenda setting effect. The correlations between the low high media literate students agenda and the media agenda are stronger than the correlations between the medium media literate students’ agenda and the media agenda. Other media exposure, different level of units of analysis usage the relevance of the information and news coverage in dramatic style may be the possibility factors determining whether or not agenda setting of newspapers takes place. With regard to framing effect, researcher finds significant relationship between media literacy and framing effect. The findings demonstrate that framing can have an effect on the way the lower media literates end up interpreting issues more than the higher media literates.